Simulated X‐ray emission in galaxy clusters with feedback from active galactic nuclei. Issue 1 (24th January 2021) - Kar Chowdhury, Rudrani; Roy, Soumya; Chatterjee, Suchetana; Khandai, Nishikanta; Sarazin, Craig L.; Di Matteo, Tiziana
Abstract : To investigate the effect of feedback from active galactic nuclei (AGN) on their surrounding medium, we study the diffuse X‐ray emission from galaxy groups and clusters by coupling the Astrophysical Plasma Emission Code (APEC) with the cosmological hydrodynamic simulation involving AGN feedback. We construct a statistical sample of synthetic Chandra X‐ray photon maps to observationally characterize the effect of AGN on the ambient medium. We show that AGN are effective in displacing the hot X‐ray emitting gas from the centers of groups and clusters, and that these signatures remain evident in observations of the X‐ray surface brightness profiles.